Bilateral Herpes Simplex Keratoconjungtivitis: A Case Report (Pusat Mata Nasional Rumah Sakit Mata Cicendo Bandung, 2022)
Introduction: Herpes Simplex Virus (HSV) is one of the DNA viruses known to infect the human eye. Herpes simplex keratitis is, in general, a unilateral disease. Simultaneous bilateral involvement is a rare occurrence that has been observed in patients with compromised immune systems. Purpose: To report a case of bilateral herpes simplex keratoconjunctivitis Case Report: A 22-year-old man arrives with the primary complaint of redness in both eyes in the last four days. The patient complained of blurred vision, tearing, and foreign body sensations. Ophthalmology examination of both eyes revealed visual acuity of 1.0 in the right eye and 0.8 in the left eye, a dendritic lesion, and a decrease in corneal sensation. Patient was diagnosed with bilateral keratoconjunctivitis HSV and was treated with acyclovir ointment, levofloxacin eye drops, acyclovir 400 mg five times a day, and vitamin C 500 mg. Discussion: Bilateral herpes simplex keratitis can occur in both immunocompromised and immunocompetent individuals. Recurrence of HSV infectious keratitis is common. Factors such as emotional stress, fever, postoperative tear dysfunction, ultraviolet (UV-A) radiation exposure, and ocular (accidental or surgical) trauma have also been related to the reactivation of the herpes simplex virus. History, physical, and laboratory examinations support the patient?s diagnosis in order to get the appropriate treatment. Conclusion: Simultaneously occurring bilateral herpetic keratitis has a high proportion of complications, either because of the greater virulence of the virus or because of altered host susceptibility. Therefore, prompt administration of medication upon diagnosis is essential to reduce the severity and frequency of viral attacks and delay the progression of corneal damage.